The Political Psychology of Citizen Satisfaction: Does Functional Responsibility Matter?. (3rd July 2019) - Jilke, Sebastian; Baekgaard, Martin
Abstract: The provision of public services is a key responsibility of elected politicians. Research suggests that citizens' satisfaction evaluations of public services are incomplete representations of service quality and performance. However, little attention has been given to the political nature of service evaluations. Based on the theory of (partisan) motivated reasoning and the literature on responsibility attribution, we argue that citizens provide more favorable evaluations of municipal services when the responsibility for these services is vested in political principals with matching partisanship. Drawing on original data from a two-wave pre-post panel survey of Danish voters in the 2017 municipal elections, we employ a difference-in-differences estimator to identify the effect of a partisan match between voters and elected municipal leaders on citizen satisfaction with municipal services. We furthermore nest a survey experiment in the panel survey to test whether partisan bias in citizen satisfaction emerges when the line of functional responsibility between political principals and public services is clear and not dispersed across multiple actors. Our findings provide support for the hypothesis of partisan bias in satisfaction evaluations. We further demonstrate the importance of clarity of responsibility; partisan bias seems to come into being when the functional responsibility of municipal leaders for public services is clear and not dispersed across multiple actors, pointing toward a possible mechanism of partisan bias in citizen satisfaction.